2006
DOI: 10.1037/h0100197
|View full text |Cite
|
Sign up to set email alerts
|

Maternal speech to children with Down Syndrome: An update.

Abstract: Recent research on maternal speech to children with Down Syndrome (DS) generally corroborates studies conducted in the 1970s and 1980s. Specifically, the characteristics of language used by parents when speaking to children with mental retardation closely matches the characteristics of language addressed to typical children with the same language age. The question remains, however, why the language of children with DS develops more slowly and sometimes never reaches adult levels. This question is examined in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In line with previous studies, we found a significant association between maternal language and child MLU (Rondal et al, 1978, 2006), but only for TD mother-child dyads. Specifically, in dyads with TD children frequencies of maternal descriptions and maternal referents to the environment were positively associated with child MLU.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies, we found a significant association between maternal language and child MLU (Rondal et al, 1978, 2006), but only for TD mother-child dyads. Specifically, in dyads with TD children frequencies of maternal descriptions and maternal referents to the environment were positively associated with child MLU.…”
Section: Discussionsupporting
confidence: 92%
“…Pino (2000) reported that mothers of children with DS used more information-salient speech with the purpose of teaching than mothers of TD children. Also the functional aspects of maternal speech appear to be influenced by child MLU in the few studies investigating this relation (Rondal, 1978, 2006) in maternal language directed to children with DS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had been once proposed that the language input directed by parents to children with Down syndrome (DS) 1 was too simplified and amounted to relative linguistic deprivation. Further research showed, however, that at corresponding developmental levels, the language addressed by parents of children with DS is not different from the language addressed by parents of TD children, neither in terms of morphosyntactic models or feedback contingent upon children's productions [31].…”
Section: Morphosyntactic Learning In Cognitive Handicapmentioning
confidence: 87%
“…by calling different animals ‘bird’, the child starts to create an implicit animal category) and children with neurodevelopmental disorders have difficulty with category formation. It is important to note, however, that Cardoso-Martins and Mervis (1985) studied only five child–mother dyads with DS, and also they did not establish a causal relationship between maternal labelling behaviours and children's language development (see Rondal & Docquier, 2006, for a critical review). Nevertheless, unconscious assumptions about what an atypical child can and cannot learn may lead parents to provide less variation in linguistic input (fewer samples) and thus a more impoverished linguistic environment.…”
Section: Specialization As An Active Processmentioning
confidence: 99%